The Role of Islamic Education Management in Implementing Character Education Through Religious Activities at MAN 2 Tasikmalaya - Fauziah Habibilah; Nursa’adah; Badrudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Character education is an important aspect in the formation of a young generation with noble character, while Islamic education management plays a key role in designing, managing, and evaluating religious activities that support this goal. This study uses a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation, which were then analyzed descriptively. The results show that Islamic education management at MAN 2 Tasikmalaya has successfully integrated character values ​​into religious activities such as religious study, congregational prayer, the habit of reading the Qur'an, and socio-religious activities. A participatory approach, visionary leadership, and consistent supervision are key factors in the success of implementing character education through religious activities. This study concludes that Islamic education management has a significant contribution in creating an educational environment that supports the holistic development of student character.